2014
DOI: 10.1371/journal.pone.0114228
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivation of Bt Corn Producing Cry1Ac Toxins Does Not Adversely Affect Non-Target Arthropods

Abstract: Transgenic corn producing Cry1Ac toxins from Bacillus thuringiensis (Bt) provides effective control of Asian corn borer, Ostrinia furnacalis (Guenée), and thus reduces insecticide applications. However, whether Bt corn exerts undesirable effects on non-target arthropods (NTAs) is still controversial. We conducted a 2-yr study in Shangzhuang Agricultural Experiment Station to assess the potential impact of Bt corn on field population density, biodiversity, community composition and structure of NTAs. On each sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 76 publications
10
24
0
Order By: Relevance
“…Therefore, diversity indices and multivariate analyses are often combined together to assess the effects of Bt crops on non-target arthropods in the field, which help to obtain a more comprehensive view of species abundance, diversity and community composition of arthropods in the field. An increasing number of studies have adopted multivariate analyses, such as PRC, CCA and RDA to compare the non-target arthropod communities of Bt crops with those of nonBt crops (Guo et al 2014;Habuštová et al 2014;Li and Liu 2013;Lu et al 2014;Svobodová et al 2013Svobodová et al , 2016. All of these studies have demonstrated that non-target arthropod community in Bt crops are similar to those found in corresponding non-Bt crops, which has been further substantiated by our multivariate analyses results.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Therefore, diversity indices and multivariate analyses are often combined together to assess the effects of Bt crops on non-target arthropods in the field, which help to obtain a more comprehensive view of species abundance, diversity and community composition of arthropods in the field. An increasing number of studies have adopted multivariate analyses, such as PRC, CCA and RDA to compare the non-target arthropod communities of Bt crops with those of nonBt crops (Guo et al 2014;Habuštová et al 2014;Li and Liu 2013;Lu et al 2014;Svobodová et al 2013Svobodová et al , 2016. All of these studies have demonstrated that non-target arthropod community in Bt crops are similar to those found in corresponding non-Bt crops, which has been further substantiated by our multivariate analyses results.…”
Section: Discussionsupporting
confidence: 82%
“…As the area under cultivation with Bt crops has steadily increased worldwide, environmental risk assessments (ERA) of Bt crops on non-target arthropods have attracted increasing attention from a number of researchers (Devos et al 2012;Guo et al 2014;Habuštová et al 2014;Romeis et al 2008). Laboratory and field studies have evaluated the effects of Bt maize on non-target arthropods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations